2018
DOI: 10.1097/eja.0000000000000766
|View full text |Cite
|
Sign up to set email alerts
|

Self-confidence and level of knowledge after cardiopulmonary resuscitation training in 14 to 18-year-old schoolchildren

Abstract: Guideline compliant (90 min) theoretical and practical CPR training improves the level of knowledge and self-confidence in 14 to 18-year-old schoolchildren. Older schoolchildren are more likely to have increased self-confidence with respect to initiating CPR. Schoolchildren with an immigrant background showed a significantly lower increase in their level of knowledge and self-confidence compared with native children. Adaptation and simplification of teaching materials and further research on educational method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 39 publications
4
67
1
6
Order By: Relevance
“…However, these studies did not investigate the extent of self-confidence deterioration between single training sessions. Another very recently published study reports sustained self-confidence at 6 months in pupils aged 14–18 years old after a 90 min BLS training, with better preservation among older pupils 21. This fact, as well as the different assessment interval, might explain the discrepancy with the findings in our study of decreased self-confidence after 9 months in pupils aged 10–17 years.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, these studies did not investigate the extent of self-confidence deterioration between single training sessions. Another very recently published study reports sustained self-confidence at 6 months in pupils aged 14–18 years old after a 90 min BLS training, with better preservation among older pupils 21. This fact, as well as the different assessment interval, might explain the discrepancy with the findings in our study of decreased self-confidence after 9 months in pupils aged 10–17 years.…”
Section: Discussioncontrasting
confidence: 99%
“…There is conflicting evidence with respect to gender-specific differences in the learning outcome ‘knowledge’ after BLS education in schools 11 13 15 18 19 21 31. Whereas two studies describe a gender-specific effect of BLS trainings on willingness to perform BLS,13 32 there is another study that did not show such an effect 21. As a result, some selection bias cannot be ruled out, and the generalisability of the data might be limited to a certain degree.…”
Section: Discussionmentioning
confidence: 98%
“…In Germany, research showed that the ability to implement practical CPR interventions among 10-year-olds was the same as among 13-year-olds [15]. However, schoolchildren aged 13 or more have greater theoretical knowledge [15,24,26]. Considering the assessed effectiveness of CPR training in schoolchildren, some advocate the introduction of CPR training between the ages of 10 and 11.…”
Section: Discussionmentioning
confidence: 99%
“…2 The 70% events of the cardiac arrest happened out of the hospital (Out-of-Hospital Cardiac Arrest/OHCA) whom the first responder was the common people such as the family members, friends, neighbors, and other people close to them. 4 The life possibility of the people who experienced the cardiac arrest could increase significantly, two to three times, using the cardiopulmonary resuscitation by the people who first found them. This would reduce the brain damage and improve the return of the circulation.…”
Section: Background and Significancementioning
confidence: 99%